2021
DOI: 10.1016/j.ajem.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on conducting emergency medicine clinical research

Abstract: The impact of COVID-19 pandemic on conducting emergency medicine clinical researchThe COVID-19 pandemic challenges the status quo of conducting emergency medicine (EM) research [1]. Research generates new knowledge for the advancement of the medical field, abiding by ethical parameters [1-3]. As EM is on the frontlines of this global crisis, the aim of this correspondence is to consider the impacts of the COVID-19 pandemic on EM clinical research.Financial burdens for EM research have been an ongoing concern p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Research during the COVID-19 pandemic employs more online survey research and also systematic literature review methods, both of which do not require face-to-face contact with informants and respondents or work in laboratories so that research with this method is widely found and is an adaptation strategy for researchers at universities in dealing with the COVID-19 pandemic [42], [43]. Moreover, research that employs secondary data with both qualitative and quantitative analysis is also the choice of researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Research during the COVID-19 pandemic employs more online survey research and also systematic literature review methods, both of which do not require face-to-face contact with informants and respondents or work in laboratories so that research with this method is widely found and is an adaptation strategy for researchers at universities in dealing with the COVID-19 pandemic [42], [43]. Moreover, research that employs secondary data with both qualitative and quantitative analysis is also the choice of researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Medical personnel such as nurses are in the top position in the types of work that are most often exposed to diseases and infections such as the risk of facing an exposure to COVID-19 (Tiasari, 2020). The high risk, according to Ehrlich, McKenney, and Elkbuli (2021), is caused by the length of interaction with patients and the large number of patients causing an increase in the number of viruses around them; these factors are exacerbated by the lack of the personal protective equipment (PPE) and lack of knowledge related to the use of the PPE. During the COVID-19 pandemic nurses sacrificed themselves to actively participate in services against the pandemic.…”
Section: Introductionmentioning
confidence: 99%